Home iv Antibiotic Therapy through a Medical Day Care Unit - Marie Gourdeau; Louise Deschênes; Martine Caron; Marc Desmarais (Canadian Journal of Infectious Diseases)
An out-patient parenteral antibiotic therapy program provided through a medical day care unit was evaluated in a tertiary care hospital. From July 11, 1988 to December 31, 1990, 122 patients were treated either on site at the unit or at home with self-administered intravenous antibiotics. In all, 142 courses of parenteral antibiotics (mostly cephalosporins and clindamycin) were given for a total of 124 infections, mostly bone and soft tissue infections (67 of 124, 54%). The duration of out-patient therapy ranged from two to 62 days with a mean duration of 9.4 days if treated at the unit, or 13.2 days in the home care model (1476 patient-days). Vein access was peripheral and catheters remained functional for an average of 4.9 days (range 0.5 to 22 days). Only two patients experienced adverse drug reactions that necessitated modification of treatment. One other case was readmitted to the hospital for surgical debridement. The average cost per patient-day was $66 compared with $375 for in-hospital therapy. This program proved to be safe, efficient, and cost-effective.